In the aftermath of trauma: Marks of stress-related psychopathology - Schür, RR (Utrecht University, 2017)
In this thesis we investigated (traumatic) stress and psychopathology with a focus on the potential roles of the hypothalamus-pituitary-adrenal (HPA) axis, the GABA system, their association, and the general genetic background of major depressive disorder (MDD) and posttraumatic stress disorder (PTSD). We first reviewed the evidence on the cortisol response to psychosocial stress across psychiatric disorders and found that sex and symptomatic state are crucial factors to consider when comparing patients with healthy controls. Whereas women with MDD or an anxiety disorder showed blunting of the cortisol stress response, men with MDD or social anxiety disorder (SAD; the most commonly studied anxiety disorder) showed an increased cortisol stress response. These aberrations were absent (in men) or attenuated (in women) in individuals remitted from MDD compared with controls. Furthermore, we investigated changes in glucocorticoid receptor (GR) exon 1F methylation over time in a military cohort deployed to Afghanistan. We showed that trauma exposure during deployment was associated with an increase in GR-1F methylation six months after deployment and that specifically increases at functionally relevant sites were associated with the development of post-deployment psychopathology. With regard to the GABA system, we evaluated the literature on in vivo brain GABA levels (as measured with proton magnetic resonance spectroscopy (1H-MRS)) across psychiatric disorders and found lower GABA levels in patients with MDD compared with controls, but not in patients remitted from MDD. Moreover, convincingly lower brain GABA levels were observed in patients with autism spectrum disorder and a trend level GABA decrease was seen in patients with schizophrenia compared with healthy individuals. Subsequently, we examined change in plasma GABA levels in relation to psychopathology and trauma exposure during deployment in a large military cohort. A rise in plasma GABA levels over time was associated with the development of psychopathology (especially depressive symptoms), but not with trauma exposure. As GABA levels rose after the development of psychopathology symptoms, it may serve as a compensatory mechanism for these symptoms. To investigate the link between the GABA (and glutamate) system and the HPA axis we used 1H-MRS to investigate changes in medial prefrontal GABA and glutamate levels in response to a psychosocial stress test and in relation to salivary cortisol levels over time in healthy individuals. We did not find evidence for an effect of stress on brain GABA or glutamate levels 30 minutes after stress onset, nor did we observe an association between the cortisol stress response and GABA or glutamate levels. Finally, we calculated polygenic risk scores based on the largest genome-wide association studies so far for MDD and PTSD and found no main effect or interaction of these score with trauma exposure during military deployment on the development of PTSD and depressive symptoms at five time points up to five years post-deployment.
Keywords: Trauma; Stress; GABA; Hypothalamus-pituitary-adrenal-axis; cortisol; psychopathology; depression; PTSD; deployment; longitudinal